2017
DOI: 10.3390/rs9070727
|View full text |Cite
|
Sign up to set email alerts
|

100 Years of Competition between Reduction in Channel Capacity and Streamflow during Floods in the Guadalquivir River (Southern Spain)

Abstract: Reduction in channel capacity can trigger an increase in flood hazard over time. It represents a geomorphic driver that competes against its hydrologic counterpart where streamflow decreases. We show that this situation arose in the Guadalquivir River (Southern Spain) after impoundment. We identify the physical parameters that raised flood hazard in the period 1997-2013 with respect to past years 1910-1996 and quantify their effects by accounting for temporal trends in both streamflow and channel capacity. Fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…This trend is in line with the general decrease of winter discharge of the Iberian rivers from the 1980s (Figure 2f). In these southern latitudes, positive NAO phases corresponded to lower winter river discharges, while negative phases captured wet years (Figure 2f) such as 2010 that was characterized by dramatic floods in the Guadalquivir basin [49]. For rivers in the north of the UK, the positive (negative) NAO phases captured many, but not all, wet (dry) years (Figure 2b).…”
Section: River-discharge Variabilitymentioning
confidence: 96%
“…This trend is in line with the general decrease of winter discharge of the Iberian rivers from the 1980s (Figure 2f). In these southern latitudes, positive NAO phases corresponded to lower winter river discharges, while negative phases captured wet years (Figure 2f) such as 2010 that was characterized by dramatic floods in the Guadalquivir basin [49]. For rivers in the north of the UK, the positive (negative) NAO phases captured many, but not all, wet (dry) years (Figure 2b).…”
Section: River-discharge Variabilitymentioning
confidence: 96%
“…Furthermore, a Leica Disto S910 laser distance meter was used as an auxiliary piece of equipment. Its ±1.00 mm accuracy and 0.5 m in 300 m make it usable in research works [46,47]. Ten control points spread out on the façade were recorded (see Figure 2).…”
Section: Data Collectionmentioning
confidence: 99%
“…Flood risk studies are typically associated with extreme hydrological events, assuming only clear water and nonerodible channels in implementing numerical codes to prepare flood risk management plans (Villarini and Smith, 2010;Alfieri et al, 2014;Nied et al, 2017). However, geomorphic processes and anthropogenic alterations of the topography (Costabile and Macchione, 2015) can mediate and increase the impacts of extreme events (Bohorquez and del Moral-Erencia, 2017). Moreover, management practices can change the catchment flow regime, determining the geomorphological behavior and response to flooding (Wheater and Evans, 2009), especially along floodplains that are subjected to cyclical erosion and deposition processes.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, additional effort is needed to integrate river morphology and vegetation coverage in the evaluation of flood risk, to better understand how the connections between channel conveyance and other flooddrivers look under different boundary conditions, such as climate, water and sediment characteristics, and in response to natural and anthropogenic alterations. Accounting for these connections in planning future flood risk management strategies could be beneficial, as recent studies have demonstrated (e.g., Bohorquez and del Moral-Erencia, 2017;Sofia et al, 2017).…”
Section: Introductionmentioning
confidence: 99%